If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 14 + 3x + -15 = 7 Reorder the terms: 14 + -15 + 2x + 3x = 7 Combine like terms: 14 + -15 = -1 -1 + 2x + 3x = 7 Combine like terms: 2x + 3x = 5x -1 + 5x = 7 Solving -1 + 5x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 5x = 7 + 1 Combine like terms: -1 + 1 = 0 0 + 5x = 7 + 1 5x = 7 + 1 Combine like terms: 7 + 1 = 8 5x = 8 Divide each side by '5'. x = 1.6 Simplifying x = 1.6
| 5(t+2)=2(t+3) | | (2x-7)(x+3)(x-2)=0 | | (4x)+(3x-8)=90 | | x+x-20=54 | | 2x^2+2y^2+8x-12y+3=0 | | 8y+3=7y-7 | | 20-5/2 | | j^2+24j+23=0 | | 2(x-3)-4x=8-3(2x-1)+11 | | 2x+16=3x-25 | | 3x-25=2(y+8) | | 64=4+6(x+4) | | g^2-13g+22=0 | | j^2+6j=0 | | d^2-50d=0 | | 17y*3= | | (-9/7)x1/2/11x(-1/6) | | 5x+58=x+26 | | (a-2)*(a-2)= | | (6ln(7))-(6ln(1))= | | 9(d-4)-6=8(d-8)+46 | | 6x+30=2x+6 | | (h+7)(h-2)h=72 | | 4(2x-1)-2(x+3)=5 | | 5(r+5)=2(r-4)+1 | | 4U^3=64u | | x(670-x)=.35 | | (670-x)/x=.35 | | =x^2+mx-2x | | 5x+12=4x+2 | | -3(4y-6)+6y=4(y+4) | | 15b^2-24b-63=0 |